Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa - Lamboj, Anton (Zootaxa, 2003)
Chromidotilapia melaniae and C. nana, two new cichlid species, are described from southern Gabon and the southern parts of the Ogooue-River system in Gabon. C. melaniae differs from congeners by a combination of coloration, morphometric and meristic characters. C. nana is the smallest known species of the genus and is distinguished from congeners in having a single row of teeth in both jaws of adults (versus multiple rows). Both new species are pair-bonding, biparental, oviphilic mouthbrooders. Intrageneric relationships of Chromidotilapia in Gabon are discussed.